Unravelling the influence of light on inshore coral and sponge recruits and their substrate communities - Gerard Ricardo; Muhammad Azmi Abdul Wahab; Eduardo Arias; Lee Bastin; Christopher Brunner; Heidi M. Luter; Matthew Nitschke; Matt Salmon; Andrew Negri (Marine Pollution Bulletin, 2026)

Increasing Hydroclimatic Whiplash Can Amplify Wildfire Risk in a Warming Climate - Daniel L. Swain; John T. Abatzoglou; Christine M. Albano; Manuela I. Brunner; Noah S. Diffenbaugh; Crystal Kolden; Andreas F. Prein; Deepti Singh; Christopher B. Skinner; Thomas W. Swetnam; Danielle Touma (Global Change Biology, 2025)

The AutoSpawner system - Automated ex situ spawning and fertilisation of corals for reef restoration - Andrea Severati; F. Mikaela Nordborg; Andrew Heyward; Muhammad A. Abdul Wahab; Christopher A. Brunner; Jose Montalvo-Proano; Andrew P. Negri (Journal of Environmental Management, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

A gis-based assessment on the vulnerability and future extent of the tropical forests of the congo basin - Quanfa Zhang; Christopher O. Justice; Mingxi Jiang; Jake Brunner; David S. Wilkie (Environmental Monitoring and Assessment, 2006)